2013
DOI: 10.1088/0004-637x/779/2/138
|View full text |Cite
|
Sign up to set email alerts
|

The Era of Star Formation in Galaxy Clusters

Abstract: We analyze the star formation properties of 16 infrared-selected, spectroscopically confirmed galaxy clusters at 1 < z < 1.5 from the Spitzer/IRAC Shallow Cluster Survey (ISCS). We present new spectroscopic confirmation for six of these high-redshift clusters, five of which are at z > 1.35. Using infrared luminosities measured with deep Spitzer/MIPS observations at 24 µm, along with robust optical+IRAC photometric redshifts and SED-fitted stellar masses, we present the dust-obscured starforming fractions, star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
293
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(322 citation statements)
references
References 122 publications
29
293
0
Order By: Relevance
“…This suggests a large fraction of quiescent galaxies and/or galaxies with low or dust-extincted SFRs as potential cluster members (see Section 5.2). Note the similarity with Brodwin et al (2013), albeit at lower redshift, who found that~40% of cluster members at < < z 1.37 1.50 are SF galaxies based on the Spitzer 24 μm emission, using an infrared-selected sample with stellar masses…”
Section: Irac Color-selection Efficiencysupporting
confidence: 73%
See 2 more Smart Citations
“…This suggests a large fraction of quiescent galaxies and/or galaxies with low or dust-extincted SFRs as potential cluster members (see Section 5.2). Note the similarity with Brodwin et al (2013), albeit at lower redshift, who found that~40% of cluster members at < < z 1.37 1.50 are SF galaxies based on the Spitzer 24 μm emission, using an infrared-selected sample with stellar masses…”
Section: Irac Color-selection Efficiencysupporting
confidence: 73%
“…For example, based on a sample of 16 spectroscopically confirmed clusters at < < z 1 1 . 5 , Brodwin et al (2013) showed that at > z 1.3 the fraction of SF cluster members increases toward the cluster centers. These results suggest that the majority of star formation actually occurs in high-density environments at early epochs, implying that environmental-dependent quenching has not yet been established at > z 1.3.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This trend continues with increasing redshift, such that at z∼1.4, the SFR in the field and in the cluster environment are indistinguishable (Brodwin et al 2013;Alberts et al 2014;Wagner et al 2015, see also Figure 5). Thus, we would expect there to be a significantly higher fraction of gas-rich galaxies in our high-z subsample than in the low-z systems, particularly in the inner cores where gas depletion is most effective at low-z.…”
Section: An Evolving Fuel Supply?mentioning
confidence: 74%
“…In addition, based upon measurements of the Hα emission from galaxies in the Snyder et al (2012) clusters, Zeimann et al (2013) infer unobscured SFRs of up to 200 M yr −1 for galaxies right down in the cluster cores. SFR measurements of the same clusters from Spitzer 24 µm observations, as well as Herschel SPIRE data, find similarly high SFRs, with the SFR in clusters increasing rapidly with redshift (Brodwin et al 2013;Alberts et al 2014).…”
Section: Trends In Galaxy Propertiesmentioning
confidence: 74%